(3LGeY GdeHGOF hGdZGjGJs - (3CHh Ydj TQa GdOjf GdMSf Hf Ydj Hf YeQ GdeQGcTj,J (B660 (3g` s ((3eMeO Hf CMeO GdCfUGQi GdNTGH s)
(3ChdgG (B:s
(3HYO GdOjHGLI aEfi deG QCjJ cKjQkG ef GdfGS jNhVhf ai hVY GdGdGJ GdadcjI hGdJMQjQ efge s
(3BNQgG (B:s
(3hUhQJgG Ydi eG JQi hgh XGgQ aGage Pdc s
(3jMJhi Ydi cKjQ ef GdLOGhd hGdQShe GdgfOSjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B203 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B286s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B24 s
Keywords: (3Gdadcs